2021
DOI: 10.3389/fpsyt.2021.625158
|View full text |Cite
|
Sign up to set email alerts
|

Down and High: Reflections Regarding Depression and Cannabis

Abstract: In light of the recent changes in the legal status of cannabis in Canada, the understanding of the potential impact of the use of cannabis by individuals suffering from depression is increasingly considered as being important. It is fundamental that we look into the existing literature to examine the influence of cannabis on psychiatric conditions, including mood disorders. In this article, we will explore the relationship that exists between depression and cannabis. We will examine the impact of cannabis on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 134 publications
0
13
0
1
Order By: Relevance
“…For instance, a 25% prevalence of depressive disorders has been reported among chronic cannabis users [ 159 , 160 ], and the numbers are even more concerning in women and in early-onset cannabis users [ 161 , 162 ]. Furthermore, the results of a meta-analysis published in 2019 showed that cannabis use in adolescence is associated with a higher likelihood of developing depression and suicide ideation in young adulthood [ 148 ].…”
Section: Divergent Central Effects Of Thc and Cbdmentioning
confidence: 99%
“…For instance, a 25% prevalence of depressive disorders has been reported among chronic cannabis users [ 159 , 160 ], and the numbers are even more concerning in women and in early-onset cannabis users [ 161 , 162 ]. Furthermore, the results of a meta-analysis published in 2019 showed that cannabis use in adolescence is associated with a higher likelihood of developing depression and suicide ideation in young adulthood [ 148 ].…”
Section: Divergent Central Effects Of Thc and Cbdmentioning
confidence: 99%
“…47 There are data suggesting that CU, particularly during vulnerable periods such as adolescence, can alter cerebral functioning and lead to changes in brain structure. 48 It is possible that the effects of CU may overlap or contribute to prominent mood symptoms (e.g., anhedonia and apathy), leading to their exacerbation or potentially confounding the diagnosis of BD or MDD. 48 In summary, what limited data exist suggest that CU is associated with a worsening of mood disorder symptoms.…”
Section: Low-moderatementioning
confidence: 99%
“…The limited success of drug discovery in the context of depression is ultimately linked to an incomplete understanding of the etiology and underlying neurobiology of this disorder. MDD is a multifactorial disorder that involves multiple interrelated causal mechanisms [212,213] including environment, genetics [214,215], and adverse life events such as early life stress [216,217]. Some genetic influences have been associated with the heritability of MDD, estimated at approximately 38% [218].…”
Section: Depressionmentioning
confidence: 99%